PENGARUH MENGGUNAKAN MODEL POWER OF TWO TERHADAP KEMAMPUAN MENULIS SISWA KELAS VIII DI SMPN 1 BANGKO TAHUN AKADEMIK 2018/2019 - a eki Kurniawan (Jurnal Tunas Pendidikan, 2019)
Writing is an activity of the human mind process that will express the contents of his soul to others or to themselves in writing. Writing is a representation of language in contextual media through the use of a set of signs or symbols. The main purpose in writing is communication. Communication in written form is that students must know the rules of language when they write. Writing in English has many rules including grammar, spelling and punctuation. Not getting good grades. Based on researchers' interviews with English teachers at Bangko 1 Bangko, the teacher said writing was one of the basic competencies that must be taught to students of all English language abilities, especially emphasized in writing narrative texts. In the syllabus of English learning in the second semester in eighth grade, it is found that students are able to: express meaning and rhetorical steps in simple short essays using various written languages accurately, and fluently to interact with the environment around retelling and narrative forms. But in reality, the students' writing ability at SMPN 1 Bangko is lacking, it makes it very difficult for students to write in English when the teacher gives an assignment. In other problems, students cannot develop their knowledge when the teacher gives practice and it is difficult to develop their ideas in essay writing.In this study, researchers used experimental research. The research sample consisted of two classes in which the second class A as an experimental class consisted of 80 students from three classes. The selected sample was class VIII A as the experimental class and control class VIII B. Both classes were used to compare the results of writing skills. To take samples from three classes, researchers used pre-tests before conducting the experiment, two of the three classes that had the closest average value were taken, after pre-testing there were two classes that had the closest average, grade VIII A got mean 53.5 and class VIII B got an average of 52.0. The experimental class was taught using the Power of Two Model on Students 'Writing Ability, and the control class without using the Power of Two Model on Students' Writing Ability. The results showed that the average score of the experimental class was higher than the control class, the average score of the experimental class was 60.75 and the average score of the control was 59.33. This means that there is a significant effect on student writing by using the Power of Two Model to teach student writing, hopefully it can overcome the above problems, so that student participation and student writing ability increase